2020
DOI: 10.18821/0869-2084-2020-65-4-239-243
|View full text |Cite
|
Sign up to set email alerts
|

Perthes Disease: Immunological Aspects

Abstract: Considering a stage of the pathological process patients (boys at the age of 8-12 years) were divided into two (2) groups. Group I included 14 patients with the fragmentation stage (Perthes disease Stage II). Group 2 included 15 children with Perthes disease Stage III (the stage of re-ossification). Perthes disease regardless of the stage of the disease was characterized by the increase in oxygen-dependent and lysosomal phagocytic activity of neutrophils, the increase in the number of early extracellular traps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…For instance, VEGF plays an important role in promoting the growth and repair of blood vessels that may be disrupted in individuals with Perthes disease (Kim et al, 2004). Additionally, the occurrence of inflammation is fundamental to the pathogenesis of Perthes disease, and previous studies have reported that genetic variations in certain inflammation-related genes, including IL-6, TLR4, TNFA, and IL-3, are associated with the development of this condition (Srzentić et al, 2014;Teplen'kiy et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…For instance, VEGF plays an important role in promoting the growth and repair of blood vessels that may be disrupted in individuals with Perthes disease (Kim et al, 2004). Additionally, the occurrence of inflammation is fundamental to the pathogenesis of Perthes disease, and previous studies have reported that genetic variations in certain inflammation-related genes, including IL-6, TLR4, TNFA, and IL-3, are associated with the development of this condition (Srzentić et al, 2014;Teplen'kiy et al, 2020).…”
Section: Figurementioning
confidence: 99%